Study of Narcotics Management in One of the Private Pharmacies in Makassar City - Mustarin, Rahmah; Utami, Yuri Pratiwi; Massolo, Selpi (International Journal of Health Sciences, 2024)
Drug management is an important aspect of management, because its inefficiency will have a negative impact on health facilities both medically and economically. Drug management includes the stages of planning, procurement, receipt, storage, delivery, destruction, control, recording and reporting. The purpose of this research is to determine the suitability of the management of Narcotic drugs in one of the Makassar City Pharmacies with the regulations stipulated in the Minister of Health Regulation No.73 of 2016 concerning pharmaceutical service standards in Pharmacies and the Food and Drug Supervisory Agency No.4 of 2018 concerning management supervision drugs, medicinal substances, narcotics, psychotropics and pharmaceutical precursors in pharmaceutical service facilities. The type of research used was descriptive using interview and direct observation methods at one of the Makassar City pharmacies. From the results of interviews and observations, the management of narcotic drugs in pharmacies is in accordance with the regulations stipulated in the Minister of Health Regulation No. 73 of 2016 concerning standards of pharmaceutical services in pharmacies and the Food and Drug Supervisory Agency No. 4 of 2018 concerning supervision of the management of drugs and materials. drugs, narcotics, psychotropics and pharmaceutical precursors in pharmaceutical service facilities.